2020
DOI: 10.3390/foods9060709
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Milk Fraud in the Chinese Market and its Relationship with Fraud Vulnerabilities in the Chain

Abstract: This study aimed to assess the prevalence of ultra-high-temperature (UHT) processed milk samples suspected of being adulterated on the Chinese market and, subsequently, relate their geographical origin to the earlier determined fraud vulnerability. A total of 52 UHT milk samples purchased from the Chinese market were measured to detect possible anomalies. The milk compositional features were determined by standardized Fourier transform-infrared spectroscopy, and the detection limits for common milk adulteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
1
7
0
2
Order By: Relevance
“…Overall, this means that the vulnerability to food fraud is often perceived as relatively low when it comes to motivations and somewhat higher in regard to opportunities, with lack of adequate controls being considered to contribute to a larger extent to fraud vulnerability. These results are in agreement with small scale assessments which compared fraud vulnerability across the fish, meat, milk, olive oil, organic banana, and spice industries in Europe [ 15 ]. These overall profiles provide a first, general impression of the large dataset.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Overall, this means that the vulnerability to food fraud is often perceived as relatively low when it comes to motivations and somewhat higher in regard to opportunities, with lack of adequate controls being considered to contribute to a larger extent to fraud vulnerability. These results are in agreement with small scale assessments which compared fraud vulnerability across the fish, meat, milk, olive oil, organic banana, and spice industries in Europe [ 15 ]. These overall profiles provide a first, general impression of the large dataset.…”
Section: Resultssupporting
confidence: 89%
“…To the best of our knowledge, there is only one study. This study deals with fraud vulnerability and prevalence in Chinese milk supply chains [ 15 ]. More extensive studies to correlate vulnerabilities and prevalence would certainly enhance fine-tuning of these types of assessments and their predictive and preventative capabilities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 In 2020, it was reported that 2% of the milk samples were adulterated in China. 10 The adulterants can be classified into two types, namely (a) economically motivated adulterants, and (b) economically motivated and harmful adulterants. 11 Water, vegetable protein, whey, and milk from different species (cow, buffalo, goat, sheep, camel, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…For example, in 2018, 7% of the milk samples failed to match the standard milk quality decided by the Food Safety and Standards Authority of India . In 2020, ∼80% of open or packed milk sampled in some areas of Pakistan were reported to be adulterated with adulterants such as water, urea, soap, and formalin. , In 2020, it was reported that 2% of the milk samples were adulterated in China . The adulterants can be classified into two types, namely (a) economically motivated adulterants, and (b) economically motivated and harmful adulterants .…”
Section: Introductionmentioning
confidence: 99%